A numerical study of nanofluid flow over a curved surface with Cattaneo–Christov heat flux influenced by induced magnetic field. (17th January 2023) - Ramzan, Muhammad; Shahmir, Nazia; Ghazwani, Hassan Ali S.; Elmasry, Yasser; Kadry, Seifedine
Abstract: This study aims to scrutinize the hydrodynamic and heat transmission of MHD water (H2 O)-based nanoliquid flow across a permeable stretched curved surface affected by an induced magnetic field. The thermal equation incorporates the Cattaneo–Christov (C-C) heat flux's influence. The partial differential equations (PDEs) that constitute the mathematical description of the flow phenomenon are developed using a curvilinear coordinate system. Koo–Kleinstreuer–Li (KKL) correlations for dynamic viscosity and thermal conductivity are used to investigate the Brownian motion and static behavior of nanoparticles in the working liquid. A MATLAB bvp4c approach is employed to compute the momentum- and energy-based ordinary differential equations, which are obtained through similarity transformation. Graphs are used to establish the impression of relevant nondimensional parameters. Further, the impact of engineering quantities is illustrated through tables. The results indicate that when enhancing the curvature parameter the induced magnetic field profile escalates. It is also inferred that when the Brownian motion is taken into account rather than just taking into account the static feature of particles, the surface drag coefficient is observed to be higher. Furthermore, when the Brownian motion of nanoparticles is evaluated rather than static motion, the heat transfer rate achieved is found to be greater.